Pharmacology of Natural Volatiles and Essential Oils in Food, Therapy, and Disease Prophylaxis - Sadgrove, Nicholas John; Padilla-González, Guillermo Federico; Leuner, Olga; Melnikovova, Ingrid; Fernandez-Cusimamani, Eloy (Frontiers in Pharmacology, 2021)
This commentary critically examines the modern paradigm of natural volatiles in ‘medical aromatherapy’, first by explaining the semantics of natural volatiles in health, then by addressing chemophenetic challenges to authenticity or reproducibility, and finally by elaborating on pharmacokinetic and pharmacodynamic processes in food, therapy, and disease prophylaxis. Research over the last 50 years has generated substantial knowledge of the chemical diversity of volatiles, and their strengths and weaknesses as antimicrobial agents. However, due to modest in vitro outcomes, the emphasis has shifted toward the ability to synergise or potentiate non-volatile natural or pharmaceutical drugs, and to modulate gene expression by binding to the lipophilic domain of mammalian cell receptors. Because essential oils and natural volatiles are small and lipophilic, they demonstrate high partition coefficients through the skin when suitably encapsulated, or if derived from a dietary item they bioaccumulate in fatty tissues in the body. In the skin or body, they may synergise or drive de novo therapeutic outcomes that range from anti-inflammatory effects through to insulin sensitisation, dermal rejuvenation, keratinocyte migration, upregulation of hair follicle bulb stem cells or complementation of anti-cancer therapies. Taking all this into consideration, volatile organic compounds should be examined as candidates for prophylaxis of cardiovascular disease. Considering the modern understanding of biology, the science of natural volatiles may need to be revisited in the context of health and nutrition.